A MATLAB/GUI based fault simulation tool for power system education - Koç, Savaş; Aydoğmuş, Zafer (My University, 2009)
A MATLAB/GUI (Graphical User Interface) based simulation tool has been developed to calculate the short-circuit fault currents in power transmission lines and to use as an educational material for courses on power system analysis. Presented program provides the calculation of three-phase (3LS), single line-to-ground (1LG), line-to-line (2LS), and double line-to-ground (2LG) faults on transmission lines. Symmetrical components of currents and voltages are used for calculations in the program. By means of the program, calculated fault currents and voltages on the fault point of the line have been presented both in per-unit and in real values. Furthermore, this calculated currents and voltages can be observed in GUI screen. In this way, an educational tool has been developed for the students to check the accuracy of their calculations and to observe the variations of waveforms. The purpose of this GUI based tool is to help the student to understand the concept of symmetrical components and short-circuit faults.
Keywords: Mühendislik; Elektrik ve Elektronik; Bilgisayar Bilimleri; Yazılım Mühendisliği